SIGNIFICANCE OF THYROID PROFILE (Serum T3, T4 & TSH) IN INFERTILE WOMEN - Sharma, Bindu; kumar, Amit; Singh, C M; Kansal, Richa (Indian Journal of Community Health, 2012)
Objective: To evaluate the relation of female infertility to thyroid dysfunction. Material & Methods: The present study was carried out in the department of Biochemistry in collaboration with the Gynae & Obst deptt., Subharti Medical College & Hospital Meerut. Serum T3, T4 and TSH estimation was done by Enzyme Linked Fluorescent Assay. Results: Serum T3 level in control group was 1.8 ± 0.64 nmol/L while it was 10.5 ± 0.5 nmol/L in hyperthyroid (p value <0.001, i.e., highly significant), 1.1 ± 0.49 nmol/L in hypothyroid (p value <0.001, i.e., highly significant). Serum T4 level in control group was 85.9 ± 26.1 nmol/L while it was 163.5 ± 3.5 nmol/L in hyperthyroid (p value <0.001 i.e., highly significant), 83.5 ± 22.4 nmol/L in hypothyroid (p value >0.05, i.e., not significant). Serum TSH in control group was 3.5 ± 1.71 mIU/L, while it was 0.14 ± 0.01 mIU/L (p value <0.001, i.e., highly significant) in hyperthyroidism, 8.4 ± 1.06 mIU/L in hypothyroidism (p value <0.001, i.e., highly significant). Out of 65 patients of study group thyroid dysfunction was associated with 25 (38.5%) infertile women. 23 (35.4%) women had hypothyroidism, 2 (3.1%) women had hyperthyroidism and 40 women (61.5%) were with euthyroid state, while in control group all the 25 women had euthyroid profile. Conclusions: Every infertile woman with ovulatory dysfunction should also investigated thyroid profile along with other investigations, to open better prospects of conception for such desperate infertile women.